KEKUATAN LELAH DUCTILE IRON THIN WALL CONNECTING ROD VESPA PX-150: KEKUATAN LELAH DUCTILE IRON THIN WALL CONNECTING ROD VESPA PX-150 - Oktaviano, Yoska; Fadhlan, Muhammad; Sulamet-Ariobimo, Rianti Dewi (Program Studi Teknik Mesin Universitas Tarumanagara, 2023)
The use of lightweight components in automotive is one of the strategies that can be taken to support energy resiliencies. Vehicles using lightweight components use less energy compared to those using the normal ones. Lightweight connecting rods have been successfully manufactured using thin wall casting technology. This piston rod is up to 26% lighter than the original component, which was made from forged steel. This thin-wall connecting rod possesses the capabilities of a normal connecting rod. A fatigue test is carried out to ensure the safety of the new design component during application. Fatigue testing was carried out by applying a dynamic force to a connecting rod of one million cycles with a force of 17KN following the ISO 10833 minimum fatigue limit without notches.